Experimental and numerical investigation of fluid flow and heat transfer in circular micro-channel - Almaneea, Abdulmajeed (Penerbit Universiti Kebangsaan Malaysia, 2020)
Nowadays, there is a large demand for many electronic devices such as the laptop, and cell phone. The heat generated by such electronic component increases due to continuous functioning. Implementing microchannel could be a good solution despite the heat from microminiature refrigerators, microelectronics, micro heat pipe spreader, fuel processing biomedical, and aerospace. Therefore, several investigations have been done to improve the performance of such continuous operating electronic devices by dissipating heat with the use of microchannels. In this study, an experimental and numerical investigation is done for the circular microchannel having the hydraulic diameter of 253 µm and 63 mm in length under the condition of constant wall temperature by submerging the microchannels in the oil at constant temperature and water is forced to pass through total 5 microchannels. Experimental conducted for various flow rates shows that the microchannel has a significant impact on the heat transfer rate for the considered flow rate. Numerical results through COMSOL 5.1 software show good agreement with the experimental results. It is observed that the heat transfer coefficient increases with the Reynolds number whereas friction factor decreases with Reynolds number. Based on numerical and experimental results, empirical correlations for friction factor and Nusselt number are suggested to provides a reasonable estimate of heat transfer in the microchannel.